BENTUK-BENTUK POSKOLONIALITAS DI INDONESIA MUTAKHIR PADA MAJALAH TEMPO - Nurhadi Nurhadi (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2011)
This article presents two points, i.e. postcolonial forms and patterns in Tempo, especially those in the section of literary book reviews. The study focused on the literary book reviews in Tempo published in 2000 – 2007. The data were collected through document analysis and were analyzed using the content analysis and qualitative descriptive technique. The findings are as follows. First, postcolonial themes in some literary book reviews in Tempo talk about: (1) stories of the Orient, (2) colonialism, (3) reviews of Western literature (including works translated into Indonesian), and (4) literary works talking about postcolonial matters. Besides, some reviews are related to: (5) Indonesian literature translated into English, (6) the encounter of the West and the East in several stories, and (7) Islam in the West. Second, the reviewers are aware of postcolonial patterns in the form of literary book reviews.